(untitled) (Historia, 2021)
English By the late 1950s, the future prospects of the Federation of Rhodesia and Nyasaland were increasingly portrayed in a pessimistic light in the British press. The Federal government chose to counter this coverage by undertaking a comprehensive public relations campaign in the United Kingdom. This article examines their decision to hire the London public relations company, Voice and Vision, and this company’s subsequent attempts to rehabilitate the Federal image between 1960 and 1963. It will be argued that although the campaign achieved limited success in some quarters, it revealed that the Federal government had misunderstood British politics, and did not grasp the erosion of the ties that might previously have secured the Federation’s future in British public sympathy only ten years earlier. Afrikaans “Voice and Vision” – Die Federasie van Rhodesië en Njassaland se Publisiteitsveldtog in Brittanje: 1960-1963 Teen die einde van die 1950’s is die toekoms van die Federasie van Rhodesië en Njassaland in ƌ toenemend pessimistiese lig deur die Britse pers uitgebeeld. Die federale regering het besluit om hierdie negatiewe mediadekking teen te werk deur ƌ omvattende publisiteitsveldtog in die Verenigde Koninkryk te onderneem. Hierdie artikel ondersoek hulle besluit om die dienste van die Londense publisiteitsmaatskappy, Voice and Vision, te bekom, en hierdie maatskappy se daaropvolgende pogings van 1960 tot 1963 om die Federasie se beeld te rehabiliteer. Daar word aangevoer dat hoewel die veldtog by sommige beperkte sukses behaal het, dit bewys het dat die federale regering Britse politiek misverstaan het en nie begryp het tot watter mate die bande, wat slegs ƌ dekade tevore nog Britse openbare simpatie Africavir die Federasie se toekoms kon verseker het, verskiet het nie.